Bell-EPR Experiments - Mondino, Luigi; Alonso, Vidal (Ciencia, 1970)
On the grounds of recent developments of the two particle interferometry, it is shown that the conditional state and the corresponding real pilot wave can provide a semiclassical account of Bell-EPR experiments in perfect agreement with the extended Feynman”˜s rule.